2013
DOI: 10.1111/j.2047-2927.2013.00146.x
|View full text |Cite
|
Sign up to set email alerts
|

The role of sympathetic and parasympathetic nerve systems on the smooth muscle of rat seminal vesicles – experimental results and speculation for physiological implication on ejaculation

Abstract: SUMMARYEjaculation is a process involving sympathetic and parasympathetic effects during different stages -emission and ejection. Some conditions of ejaculation dysfunction are associated with autonomic nerves. However, the exact effects of autonomic nerves on ejaculation are not well defined. Autonomic agonists induce different recorded trace patterns of seminal vesicular contraction. The different traces contain different components of phasic and tonic contraction, which may have physiological implications. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
7
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 29 publications
2
7
0
Order By: Relevance
“…However, other brain regions (eg the bed nucleus of stria terminalis, the nucleus paragigantocellularis, and the medial preoptic area) and multiple neurotransmitter receptors (eg opioid, serotonin, and α1a receptors) are also confirmed to participate in the regulation of ejaculation 22,32‐34 . These receptors and their neurotransmitters form complex networks of interactions, and our present results are probably an account of the balance of multiple effects.…”
Section: Discussionsupporting
confidence: 52%
“…However, other brain regions (eg the bed nucleus of stria terminalis, the nucleus paragigantocellularis, and the medial preoptic area) and multiple neurotransmitter receptors (eg opioid, serotonin, and α1a receptors) are also confirmed to participate in the regulation of ejaculation 22,32‐34 . These receptors and their neurotransmitters form complex networks of interactions, and our present results are probably an account of the balance of multiple effects.…”
Section: Discussionsupporting
confidence: 52%
“…Anatomy studies demonstrate that the main sympathetic signals to the accessory sex gland consist of the lumbar splanchnic nerve, caudal mesenteric plexus, hypogastric nerve, pelvic plexus, and its branches (Kihara et al, 1998). Recently, some studies have found that the sympathetic pathway is mainly through the a1a receptor, and the a1a antagonist has therapeutic potentials for premature ejaculation (Cl ement et al, 2006;Sato et al, 2012;Hsieh et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…The autonomic innervation may mainly underlie the synthesis of Bu‐Gs secretion (Geuze & Slot, ). Considering that synthesis and release of secretion of others accessory glands, such as seminal vesicles, only depend on autonomic control (Hsieh et al ., ), it seems that the Bu‐Gs are the unique accessory sexual glands controlled by somatic and autonomic innervation.…”
Section: Discussionmentioning
confidence: 99%